2020
DOI: 10.1101/2020.12.16.423118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling conformational state dynamics and its role on infection for SARS-CoV-2 Spike protein variants

Abstract: The SARS-CoV-2 Spike protein needs to be in an open-state conformation to interact with ACE2 as part of the viral entry mechanism. We utilise coarse-grained normal-mode analyses to model the dynamics of Spike and calculate transition probabilities between states for 17081 Spike variants. Our results correctly model an increase in open-state occupancy for the more infectious D614G via an increase in flexibility of the closed-state and decrease of flexibility of the open-state. We predict the same effect for sev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…This observation indicated that the D614G mutant may perturb hinge clusters and alter functional movements in the closed S-RRARS trimer, potentially priming protomers in the S protein for transition to the open form. These findings showed an agreement with previous studies suggesting the increase in the open state preferences for the D614G mutation due to the increased flexibility of the closed state and the enhanced rigidification of the open form 52. Indeed, while local conformational mobility profiles are similar for the native S-D614…”
supporting
confidence: 93%
See 2 more Smart Citations
“…This observation indicated that the D614G mutant may perturb hinge clusters and alter functional movements in the closed S-RRARS trimer, potentially priming protomers in the S protein for transition to the open form. These findings showed an agreement with previous studies suggesting the increase in the open state preferences for the D614G mutation due to the increased flexibility of the closed state and the enhanced rigidification of the open form 52. Indeed, while local conformational mobility profiles are similar for the native S-D614…”
supporting
confidence: 93%
“…It is worth noting that in agreement with several computational studies advocating for the "openness" mechanism 50 computational study. 52 Based on these preliminary results, we suggested a hypothesis that the D614G substitution may cause a cascade of small and subtle changes in both the intra-and…”
Section: Dynamic-based Modeling Of Residue Interaction Network and Comentioning
confidence: 85%
See 1 more Smart Citation
“…96 Coarse-grained normal mode analyses combined with Markov model and computation of transition probabilities characterized the dynamics of the S protein and the effects of mutational variants D614G and N501Y on protein dynamics and energetics. 97 Using time-independent component analysis (tICA) and protein networks, another computational study identified the hotspot residues that may exhibit long-distance coupling with the RBD opening, showing that some mutations may allosterically affect the stability of the RBD regions. 98…”
Section: Sars-cov-2 S Protein Between a Spectrum Of Closed And Receptmentioning
confidence: 99%
“…In the case of B.1.1.7, a series of mutations in eight sites including D614G appeared in the spike protein: ∆69∆70, ∆144∆145, N501Y, A570D, P681H, T716I, S982A, and D1118H (https://www.gisaid.org; GISAID, accessed on 1 December 2020). Among them, ∆69∆70 and N501Y in B.1.1.7 lineage have been shown to cause a conformational change in the spike protein and have higher infectivity than D614G, suggesting that they may increase transmissibility and alter antigenicity [10,11]. Remarkably, B.1.351 contains additional two mutations, K417N and E484K, in receptor binding motif (RBM) of the RBD region and those may potentially induce a conformational change of the spike protein, and subsequently increase the infectivity of B.1.351 than other lineages.…”
Section: Introductionmentioning
confidence: 99%